HYPERTENSION RISK FACTORS AND CARDIOVASCULAR HEALTH IN COLLEGE STUDENTS - Figueroa López, Carlos Gonzalo; Ramos del Río, Bertha (Anales de Psicología / Annals of Psychology, 2006)
The goal was to determine the hypertension risk factors and cardiovascular health in college students. 110 students were divided in: a) cases group (n=52) with hypertension family antecedent, and b) control group (n=58) without hypertension family antecedent. Both groups were evaluated with the Hypertension Family Antecedent Inventory and the Hypertension Risk Factors Inventory. The risk factors that were reported in both groups were: diabetes family antecedent, high intake of fat food, stressful environment perception, and stressful personality. It is discussed that he hypertension risk factors reported in the college students indicates that this is a vulnerable group to suffer from cardiovascular disease. Also, the absence of risk factors (v.gr. smoking, alcohol) in this group is an opportunity for the psychologist to prevent diseases and control the risk factors through, for example, the cardiovascular health promotion.